2016
DOI: 10.1038/ismej.2016.155
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of antibiotic and metal resistance genes revealed in complete genome collection

Abstract: The high frequency of antibiotic resistance is a global public health concern. More seriously, widespread metal pressure in the environment may facilitate the proliferation of antibiotic resistance via coselection of antibiotic resistance genes (ARGs) and metal resistance genes (MRGs). Given the lack of comprehensive understanding of the ARG and MRG coselection, in this study both abundance relationship and genetic linkage between ARGs and MRGs were rigorously investigated by performing a genomic analysis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(205 citation statements)
references
References 72 publications
11
189
1
4
Order By: Relevance
“…High quality ARGs (High): A UNI-gene is tagged with a "High" annotation factor if it has ≥ 90% identity to a CARD/ARDB-ARG over its entire length. This similarity cutoff has been used in other studies to identify relevant ARGs (Pal et al, 2015;Li et al, 2017) and is stricter than that used in the construction of the ARDB database (Liu and Pop, 2009).…”
Section: Uniprot Gene Annotationmentioning
confidence: 99%
“…High quality ARGs (High): A UNI-gene is tagged with a "High" annotation factor if it has ≥ 90% identity to a CARD/ARDB-ARG over its entire length. This similarity cutoff has been used in other studies to identify relevant ARGs (Pal et al, 2015;Li et al, 2017) and is stricter than that used in the construction of the ARDB database (Liu and Pop, 2009).…”
Section: Uniprot Gene Annotationmentioning
confidence: 99%
“…We further searched ARGs in all available NCBI 15,738 plasmids and other mobile genetic element (MGE) databases 35,36 by usearch v11.0, diamond 0.9.24 and blast 2.5.0+ [62][63][64] . The search cutoff was set for genomes and MGEs as e-value 1e-5, 90% aa similarity over 80% aa hit length; and for metagenomes as e-value 1e-7, 80% aa similarity over 75% aa hit length 7,8,37,65 . The abundance of ARGs was normalized into copy of genes per bacterial cell (ARGs-OAP 7,8 ) using Equation 1.…”
Section: Methodsmentioning
confidence: 99%
“…Metals such as lead, copper, zinc, cadmium, and metalloid arsenic are often used in agriculture and aquaculture (Singer, Shaw, Rhodes, & Hart, 2016). Since resistance to antibiotics and metals can share certain mechanisms (Singer et al, 2016), the phenomenon called coselection between them has been reported, and the stress of widespread metals in the environment may promote this phenomenon (Li, Xia, & Zhang, 2017). Especially, Cu and Zn that were reported to have an extensive positive correlation with antibiotic resistance (Ji et al, 2012;Wang et al, 2016;Zhu et al, 2013) in the samples from livestock farms.…”
Section: Correlations Between Antibiotic Resistance and Abiotic Facmentioning
confidence: 99%